Comparison of divergent breeding management strategies in two species of semi-captive eland in Senegal - Kubátová, Anna; Štochlová, Kateřina; Brandlová, Karolína; Jůnková Vymyslická, Pavla; Černá Bolfíková, Barbora (Scientific reports, 2020)
Breeding management of small populations may have a critical influence on the development of population characteristics in terms of levels of genetic diversity and inbreeding. Two populations of antelope sister species - Critically Endangered Western Derby eland (Tauroragus derbianus derbianus) and non-native Least Concern Cape eland (Taurotragus oryx oryx) bred under different management strategies were studied in Senegal, Western Africa. The aims of the study were to compare the population genetic parameters of the two species and to test for the presence of interspecific hybrids. In total, blood and tissue samples from 76 Western Derby elands and 26 Cape elands were investigated, using 12 microsatellite markers. No hybrid individuals were detected in the sampled animals within the multispecies enclosure in Bandia Reserve, Senegal. The parameters of genetic polymorphism indicated much lower genetic diversity in Western Derby elands compared to Cape elands. On the other hand, the coefficient of inbreeding was low in both species. It is hypothesized that this could be a positive effect of strict population management of Western Derby elands, which, despite the loss of genetic diversity, minimizes inbreeding.
Keywords: Senegal; antilopy; Antelopes; Polymorphism, Genetic; zachování přírodních zdrojů; zvířata; Breeding; Microsatellite Repeats; polymorfismus genetický; chov; Conservation of Natural Resources; mikrosatelitní repetice; Animals